Β2‐Adrenergic Receptor Solutions for Structural Biology Analyzed with Microscale NMR Diffusion Measurements1. Issue 1 (24th October 2012) - Horst, Reto; Stanczak, Pawel; Stevens, Raymond C.; Wüthrich, Kurt
<x xml:space="preserve">Abstract</x> Microcoil NMR measurements were performed to determine the final composition of solutions of the β2‐adrenergic receptor (β2AR) reconstituted with a detergent and to study the hydrodynamic properties of the detergent micelles containing β2AR (see picture). Standards are established for the reproducible preparation of G‐protein‐coupled receptor solutions for crystallization trials and solution NMR studies.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>